School attendance in multi-grade classes in the city of Buenos Aires: representation of teachers in the light of the rural education policy - Ana Paula de Holanda Cavalcanti; Waldênia Leão de Carvalho (Universidade Federal do Norte do Tocantins, 2021)
This narrative talks about the education of the countryside (rural) and the development of the pedagogical practice in the multi-grade classes in the city of Buenos Aires / PE. The full-time teachers made a research through on visits (in loco), with the application of a semi-structured interview, an open quiz and meetings with the focus group. Analyzes issues regarding working conditions of teachers of multigraded classes from rural areas. The text presents reflections on the conditions of teaching profession through data collected by questionnaire applications and narrative interviews. Based on the research results we identified in our first category of analysis and the formative expectations resulting the continued formation, the political commitment, the pedagogical practices, social and educational, the positive feeling related to the formation that arouse changes and continuity of the formation. The practice of rural teachers are based on a different approach from the conception and founded on educational policy. The main contributions of the study relate to the "lessons" learned from these teachers know-hows as a possibility of the systematization and production of a powerful academic knowledge for the formulation and development of public policies consistent with the reality of schools in rural areas.